Repair of Alkylated Bacteriophage T4 Deoxyribonucleic Acid by a Mechanism Involving Polynucleotide Ligase - Baldy, Marian W. (1971)
Methyl methanesulfate-induced lesions in bacteriophage T4 are repaired primarily by a mechanism involving polynucleotide ligase. Apparently, other recombinational and ultraviolet repair functions aren't involved.